Drugs in School: analysis of social voices - João Paulo Pereira Barros; Veriana de Fátima Rodrigues Colaço (Universidade Federal do Rio Grande do Sul, 2014)
This article aims to analyze social voices at play in the production of meanings about drugs among adolescents in a group discussion on health in the school context. Based on Public Health and the legacy of Vigotski e Bakhtin on the processes of signification, data for a Master thesis, developed by means of participant observation and a discussion group in a public school in Fortaleza/CE, are used. The results indicate tensions between social voices on the claims of adolescents about drugs, highlighting the strength with which a speech alluding to the war on drugs and prohibitionist strategies voices still circulate in the school context, despite the emergence of the harm reduction perspective.